Risk Factors of Stroke in Indonesian Population: Literature Review - Rahmania Ambarika; Mohammad Saifulaman; Apriyani Puji Hastuti; Anggraini, Novita Ana (Journal Of Nursing Practice, 2023)
Background: Stroke is a major cause of death and disability in Indonesia. Stroke requires high-quality, fast, and precise management to prevent and avoid disability and death. Stroke can be prevented by adequately controlling the risk factors and encouraging healthy lifestyles. Efforts are needed to organize health promotion programs at the community level. More and a better distribution of neurologists and neuro interventionalists is needed. Purpose: The purpose of this research is to review risk factors of stroke patient. Methods:  We included English materials published between Science Direct, PubMed, Research Gate, and Google Scholar that were used to find studies related to stroke dan risk- factor between 2016- 2022. Results: In general, risk factor of stroke are sosiodemographic factor, biological factor, lifestyle factor, other condition and other factor can cause stroke. Stroke divide into stroke infark and stroke hemoragic. Risk factor of stroke infark are non- modifiable factor (age, sex, ethnicity, genetic) and modifiable risk factors (hypertension, current smoking, waist to hip ratio, diet, alcohol consumption). Risk factor of stroke hemoragic are non- modifiable factor (age, sex, ethnicity, genetic) and modifiable risk factors (hypertension, current smoking, waist to hip ratio, diet, alcohol consumption, physical inactivity, hyperlipidemia, diabetes, cardiac causes, apolipoprotein B to A1). Conclusion: Review of discharge planning can be influenced by several factors: individual characteristics (clients' potential with special needs early, motivation), family factors (social resources, home environment), health care system (teaching home care skills with community/ hospital professionals. These factors will affect the implementation of discharge planning in health services which is hospital accreditation.